2007
DOI: 10.1080/02770900601182343
|View full text |Cite
|
Sign up to set email alerts
|

Success of a Comprehensive School-Based Asthma Intervention on Clinical Markers and Resource Utilization for Inner-City Children with Asthma in Chicago: The Mobile C.A.R.E. Foundation's Asthma Management Program

Abstract: Children with asthma in low-income households in Chicago were participants in a school-based mobile van clinic, Mobile C.A.R.E. Our objective was to investigate whether long-term follow-up changed clinical markers and resource utilization. Children were evaluated by a pediatrician in a mobile allergy clinic and classified and treated based on National Asthma Education and Prevention Program (NAEPP) guidelines. Intervention consisted of assessment of allergic environment with avoidance recommendations, institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Despite significant improvement in asthma control from program enrollment, maintenance of WCA was highly variable and affected by several factors. [38][39][40][41][42][43][44][45] In our study, adherence to prescribed controller therapy was the most significant factor associated with maintenance of WCA. Comparable findings have been widely reported.…”
Section: Discussionmentioning
confidence: 83%
“…Despite significant improvement in asthma control from program enrollment, maintenance of WCA was highly variable and affected by several factors. [38][39][40][41][42][43][44][45] In our study, adherence to prescribed controller therapy was the most significant factor associated with maintenance of WCA. Comparable findings have been widely reported.…”
Section: Discussionmentioning
confidence: 83%
“…[9] A Chicago study on a school-based asthma intervention investigated long-term follow-up impact on clinical markers and resource utilization. [10] Their fi ndings suggested that in children who had four follow-up visits, clinical symptoms were improved and health care utilization was reduced to the highest degree. Comparisons of the intervention group and non-intervention group showed that the AEI resulted in improved self-esteem and disease control together with gaining better quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies describe successful school-centered interventions, including education for students and parents, 15,16,[21][22][23][24][25][26][27][28] case management, 25,27 enhanced communication with providers, 15,21,26,27 access to providers in school-based health centers 27,29,30 or as consults, 31,32 provision of asthma action plans, 15,23 directly observed therapy, 32,33 and home visits. 27 These programs have shown improvements in asthma control and have different strengths, but many have small numbers and lack sustainability mechanisms.…”
Section: The Dpsmentioning
confidence: 99%